Connectivity as a New Paradigm in Education in the Digital Era: Technology Integration for Network-Based Learning - Arwan, Arwan (Jurnal Ilmiah Profesi Pendidikan, 2024)
This study aims to explore the application of connectivity as a new paradigm in digital-age education, with a focus on the integration of technology for network-based learning. The problems raised are the low involvement of students in the traditional learning process and the challenges faced in implementing technology in education. The method used was a mixed approach, which included a quantitative survey of 100 students and teachers, as well as qualitative interviews with 50 teachers and 20 education administrators in different countries. The results showed that connectivity significantly increased student engagement, with 67% of students feeling more engaged when using technology. In addition, the role of teachers is transformed into facilitators who support students in the learning process, and collaboration between students has increased significantly. However, infrastructure challenges, such as the digital divide and limited access to technology, remain major obstacles, especially in developing countries. The study concludes that the application of connectivity has great potential to improve the quality of education, but there is a need for investment in infrastructure and sustainable teacher training. The suggestions provided include the development of inclusive education policies, the adjustment of learning strategies according to cultural contexts, and the need for further research to explore the long-term impact of connectivity in education.